2018
DOI: 10.1186/s12870-018-1571-3
|View full text |Cite
|
Sign up to set email alerts
|

Proline synthesis in developing microspores is required for pollen development and fertility

Abstract: BackgroundIn many plants, the amino acid proline is strongly accumulated in pollen and disruption of proline synthesis caused abortion of microspore development in Arabidopsis. So far, it was unclear whether local biosynthesis or transport of proline determines the success of fertile pollen development.ResultsWe analyzed the expression pattern of the proline biosynthetic genes PYRROLINE-5-CARBOXYLATE SYNTHETASE 1 & 2 (P5CS1 & 2) in Arabidopsis anthers and both isoforms were strongly expressed in developing mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 59 publications
(78 reference statements)
1
44
0
Order By: Relevance
“…This had been revealed by increased levels of reactive oxygen species in leaves of stressed p5cs1 mutants, and by root growth being more sensitive to NaCl- or PEG-induced osmotic stress compared to wildtype plants ( Székely et al., 2008 ; Sharma et al., 2011 ). Expression of P5CR and at least one isoform of P5CS are essential for sexual reproduction in Arabidopsis, indicating that plants have no alternative pathways to synthesize proline ( Funck et al., 2012 ; Mattioli et al., 2012 ; Mattioli et al., 2018 ). Homozygous p5cs1 mutants that were additionally heterozygous for a p5cs2 mutation had very low proline content and root growth was reduced due to fewer cell divisions in the meristematic zone of the root tip ( Biancucci et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…This had been revealed by increased levels of reactive oxygen species in leaves of stressed p5cs1 mutants, and by root growth being more sensitive to NaCl- or PEG-induced osmotic stress compared to wildtype plants ( Székely et al., 2008 ; Sharma et al., 2011 ). Expression of P5CR and at least one isoform of P5CS are essential for sexual reproduction in Arabidopsis, indicating that plants have no alternative pathways to synthesize proline ( Funck et al., 2012 ; Mattioli et al., 2012 ; Mattioli et al., 2018 ). Homozygous p5cs1 mutants that were additionally heterozygous for a p5cs2 mutation had very low proline content and root growth was reduced due to fewer cell divisions in the meristematic zone of the root tip ( Biancucci et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, when we further investigated the pap2 mutants, we found that deletion of PAP2 severely affects pollen viability with a corresponding decrease to floral proline content (Figure 4). Previous studies demonstrated that failure of proline accumulation in flower, anther and pollen disrupts pollen development and maturation as the development of pollen cell wall and microspore is compromised (Mattioli et al, 2008(Mattioli et al, , 2009b(Mattioli et al, , 2012(Mattioli et al, , 2018. The level of pollen proline content appears to positively correlate with pollen viability and fertility (Mattioli et al, 2018).…”
Section: Discussionmentioning
confidence: 94%
“…The site of inorganic N reduction for amino acid synthesis can occur either in roots or source leaves, depending on plant species (Lam et al, ; Lam, Coschigano, Oliveira, Melo‐Oliveria, & Coruzzi, ; Tegeder & Rentsch, ). Amino acids in sink tissues mostly come from leaf to sink partitioning, but some amino acids like proline can be synthesized in sinks such as anthers and pollen and contribute to overall stigma proline content and male fertility (Fang, Fu, Gong, & Chai, ; Mattioli et al, ; Szekely et al, ). This is in line with evidence where (a) proline synthesis genes P5CS1 and P5CS2 are expressed in anthers and pollen grains (Mattioli et al, ; Sangu, Tibazarwa, Nyomora, & Symonds, ; Szekely et al, ), (b) pollen total amino acids are composed of ~26% proline but only ~3% proline in leaves (Chiang & Dandekar, ), (c) phloem amino acid content at reproductive stage has less proline than at vegetative stage of wild‐type Arabidopsis (Santiago & Tegeder, ), and (d) transcript abundance of proline synthesis genes is downregulated in cytoplasmic male sterile plants (Fang et al, ).…”
Section: Role Of C and N Metabolites In Anther And Pollen Developmentmentioning
confidence: 99%
“…Changes in amino acid synthesis, including proline, and accumulation throughout anther development were shown to be essential for maintaining male fertility and that reduced synthesis of amino acids is accompanied by abnormal tapetum development (Fang et al, ). Analysis of Arabidopsis p5cs1 and p5cs2 mutants reveals impaired pollen development and reduced pollen viability (Mattioli et al, ; Mattioli, Biancucci, Lonoce, Costantino, & Trovato, ). Recent transcriptomic approaches support the idea that amino acid and proline metabolism in male reproductive tissues are essential for pollen development and viability (Ji et al, ; Yang et al, ).…”
Section: Role Of C and N Metabolites In Anther And Pollen Developmentmentioning
confidence: 99%